How do I solve 15+5-5/12. please give me the steps

Answered by answersmine:

1) You must do division first. So divide 5/12 and get .41666666... 
2) Then you add 15+5 and get 20.
3) Finally you subtract 20 and .41666666... and you get 19.5833333...
4) you can simplify 19.583333... to 19.584 if you need to.
Post your answer

Related questions in Mathematics

A complex number, (a + bi), multiplied by (2 + 3i) and added to -i gives the product of (-11 + 5i) and (1 – i).a = and b =

Answer:

Hence, we have:

               a= 3 and b= 4

Step-by-step explanation:

It is given that:

A complex number, (a + bi), multiplied by (2 + 3i) and added to -i gives the product of (-11 + 5i) and (1 – i).

i.e.

(a+ib)(2+3i)-i=(-11+5i)(1-i)\\\\i.e.\\\\a(2+3i)+ib(2+3i)-i=-11(1-i)+5i(1-i)\\\\i.e.\\\\2a+3ai+2bi+3bi^2-i=-11+11i+5i-5i^2

Since, we know that :

i^2=-1

Hence, we have:

2a+3ai+2bi-3b-i=-11+11i+5i+5\\\\i.e.\\\\(2a-3b)+i(3a+2b-1)=-11+5+11i+5i\\\\i.e.\\\\(2a-3b)+i(3a+2b-1)=-6+16i

i.e. we have:

2a-3b=-6---------(1)

and

3a+2b-1=16\\\\i.e.\\\\3a+2b=16+1\\\\i.e.\\\\3a+2b=17------------(2)

On multiplying equation (1) by 2 and equation (2) by 3 we get:

13a=39\\\\i.e.\\\\a=3

on putting the value of a into equation (1) we get:

2\times 3-3b=-6\\\\i.e.\\\\6-3b=-6\\\\i.e.\\\\-3b=-6-6\\\\i.e.\\\\-3b=-12\\\\i.e.\\\\b=4


Solve 60=10√y-3A.y= -39B.y= 39C.y= 39,-39D.y= -10,39

60=10√(y-3)
60²=(10√(y-3))²
3600=100(y-3)
3600=100y-300
100y=3600+300
100y=3900
y=3900/100
y=39

we have to chek the possible answer:
10√(39-3)=10√36=10(6)=60

Answer: B.  y=39


How to solve this math question

(2x - 1) + (x + 4) = 12

2x - 1 + x + 4 = 12

3x + 3 = 12

3x = 12 - 3

3x = 9

x = 3

:)

X^2+10x-7 / x^2+10x+25=0 how do i solve for x?

You just have to solve the next equation:
x²+10x-7=0
Because, if the numerator is equal to "0", then the next expression
(x²+10x-7) /( x²+10x+25)=0

Therefore:
x²+10x-7=0
x=[-10⁺₋√(100+28)]/2=(-10⁺₋√128)/2=(-10⁺₋8√2)/2=-5⁺₋4√2
We have two possible solutions:

x₁=-5-4√2
x₂=-5+4√2

Now, we have to check these possible solutions.
Remember the denominator cannot be equal to "0".

if x=-5-4√2

[(-5-4√2)²+10(-5-4√2)-7] / [(-5-4√2)²+10(-5-4√2)+25]=0/32=0

Therefore: x=-5-4√2 is a solution.

if x=-5+4√2

[(-5+4√2)²+10(-5+4√2)-7] / [(-5+4√2)²+10(-5+4√2)+25]=0/32=0

Therefore: x=-5+4√√2 is a solution.

Answer: we have two solutions for x:
x₁=-5-4√2
x₂=-5+4√2






Given: F(x) = 2x - 1; G(x) = 3x + 2; H(x) = x 2 Find F{G[H(2)]}

F{G[H(2)]} = F{G[2*2]} = F{G[4]} = F{3*4+2} = F{14} = 2*14-1 = 27

How do I solve for x ?X +8=-15

Solve for x; in order to do that you must subtract 8 from both sides so x is by itself; the answer is -23

Solve. x-3y+2z=1 -x+4y-4z=1 5x-y+6z=9 Write answer in the form (x,y,z).

  1x - 3y + 2z = 1 →  1x - 3y + 2z = 1
 -1x + 4y - 4z = 1 → -1x + 4y - 4z = 1
 5x - 1y + 6z = 9 →           y - 2z = 2

  1x - 3y + 2z = 1 
 -1x + 4y - 4z = 1 → -1x + 4y - 4z =  1 → -5x + 20y - 20z = 5
 5x - 1y + 6z = 9 → 5x - 2y + 6z = 9 →  5x -     1y +   6z = 9
                                                                           19y - 14z = 14

    y -  2z =  2 → 19y - 38z = 38
19y - 14z = 14 → 19y -  14z = 14
                                   -24z = 24
                                    -24    -24
                                         z = -1
   y - 2z = 2
y - 2(-1) = 2
    y + 2 = 2
        - 2 - 2
          y = 0

     x - 3y + 2z = 1
x - 3(0) + 2(-1) = 1
         x - 0 - 2 = 1
               x - 2 = 1
                 + 2 + 2
                    x = 3

(x, y, z) = (3, 0, -1)

Explain how the two steps of mving the decimal and multipying by the power of 10 leave the value of the orginal number unchanged

Multiplying by the power of 10 will always move the value of the original number to the left without changing the original number. Lets say you have 2.06 and u multiply it by 10^4 power (which also equals 10000) you would end up with 20600 because when you multiply by the power of 10 however many zeros you end up with you add to the end of the original value which in this case will take two zeros to move 2.06 into 206 and then you add two zeros onto the end which leaves you with 20600. For anther example, 567 x 10^2 = 567 because 10^2 equals 100 and if you add those two zeros you get from 100 to 567 you get 56700 with the original value unchanged because when multiplying by the power of 10 you only add 0's to the number.


Sorry if that was super confusing /: I tried my best (not that good at explaining) hope I helped though (:

Can show me work to the answer that solves these problems

1634/19= 86

19 goes into 16 0 times so you now look at 163
19 goes into 163 8 times (19x8=152) 163-152=11
Bring down the 4 turning 11 into 114
19 goes into 114 6 times (19x6=114)
You answer will be 86.
If you check your work you will find that 86x19= 1634

I hope this helps.

Solve for w. 3w+8/2=25 Enter your answer in the box. Please help me!!

I think it is
 \frac{3w+8}{2} =25
multily both sides by 2
3w+8=50
mins 8 both sides
3w=42
divide both sides by 3
w=14

A fossilized leaf contains 15% of its normal amount of carbon 14. How old is the fossil (to the nearest year)? Use 5600 years as the half-life of carbon 14. Solve the problem. A. 35,828 B. 15,299 C. 1311 D. 21,839

Answer:

Option B - 15299

Step-by-step explanation:

Given : A fossilized leaf contains 15% of its normal amount of carbon 14. Use 5600 years as the half-life of carbon 14.

To find : How old is the fossil (to the nearest year)?

Solution :

Let the normal or initial amount of carbon be A,

According to the question,

An exponential function form f(t)=ab^t

Where, a is the initial i.e, a=A

A fossilized leaf contains 15% of its normal amount of carbon 14.

So, f(t)=15% of A

i.e, f(t)=0.15A

b is half-life of Carbon-14 b=0.5

and t is the time span or age of the fossil in years.

Substitute all the values in the formula,

0.15A=A(0.5)^t

\frac{0.15A}{A}=(0.5)^t

0.15=(0.5)^t

Taking log both side,

\log(0.15)=t\log(0.5)

t=\frac{\log(0.15)}{\log(0.5)}

t=2.73

For 5600 years the age of the fossil is t=2.73\times 5600=15288

Therefore, Approximately Option B is correct.

The fossils are 15299 years old.


Use the quadratic formula to solve 9x^2+6x-17=0 A.X=-1,-5B.X=-1+3√2 /3C.X=3+√14 /10D.X=-6+√31 /2

Answer:

option (b) is correct.

x_1=\frac{-1+3\sqrt{2}}{3},\:x_2=-\frac{1+3\sqrt{2}}{3}

Step-by-step explanation:

Given  equation 9x^2+6x-17=0

We have to solve the given quadratic equation using quadratic formula.

For the given standard quadratic equation ax^2+bx+c=0

Quadratic formula is given as x_{1,\:2}=\frac{-b\pm \sqrt{b^2-4ac}}{2a}

Comparing with given quadratic equation, we have a = 9, b = 6 and c = -17

Substitute in quadratic formula, we have,

x_{1,\:2}=\frac{-6\pm \sqrt{6^2-4\cdot \:9\left(-17\right)}}{2\cdot \:9}

Simplify , we have \sqrt{6^2+4\cdot \:9\cdot \:17}=\sqrt{648}

we get,

x_{1,\:2}=\frac{-6\pm\sqrt{648}}{2\cdot \:9}

Also, \sqrt{648} =\sqrt{3^4\cdot \:2^3}=18\sqrt{2}

we have,

x_{1,\:2}=\frac{-6\pm 18\sqrt{2}}{2\cdot \:9}

Thus, seperating both facotors, we have,

x_{1}=\frac{-6\+18\sqrt{2}}{2\cdot \:9}  and x_{2}=\frac{-6\-18\sqrt{2}}{2\cdot \:9}

Simplify, both we get,

x_1=\frac{-1+3\sqrt{2}}{3},\:x_2=-\frac{1+3\sqrt{2}}{3}

Thus, option (b) is correct.


Name the values of the given digits in each number the 2's in 6,228

The 8 is ones place. The 2 in the tens place and the2 is hundred place and the 6 is in the thousand place

The point P is on the unit circle. Find P(x, y) from the given information. The x-coordinate of P is 8 17 and the y-coordinate is positive. P(x, y) = ?

I always understood the unit circle to have a radius of 1 and be centered on the origin (0,0).  That there are two x coordinates confuses me.  Neither 8 nor 17 is an x value for a line passing through the unit circle, so I'm going to guess "8/17" is the actual x coordinate (which is between -1 and 1).  P(8/17,y) = x^2 + y^2 = 1.

289/289 - 64/289 = 225/289.  The square root of that (positive since y is positive) yields 15/17.  P(x,y) = 8/17, 15/17.

Solve. 3x-4y=-5 -x+2y=3 Write answer in the form (x,y).

3x-4y=-5
-x+2y=3
Multiply the second by one:
3x-4y=-5
-2x+4y=6
Combine the equations:
x = 1
Substitute x and solve for y:
-2*1+4y=6
-2+4y=6
4y=8
y=2
Answer:
(1,2)